The English E-module Based on Mind Mapping to Enhance Student Achievement: A Study on Seventh Grade - Rosalin Tanaiyo; Karmila Machmud; Rahman Taufiqrianto Dako (Universitas Pendidikan Ganesha, 2023)
The learning model applied today still uses conventional methods. Whereas today's students are those born and lived in the era of technological development, meaning they are the Gen-Z generation. Therefore, this study aims to develop a mind mapping-based English e-module that suits students' needs to improve their understanding of English lessons. The research method refers to Research and Development using 4D model development. Participants in this study were class VII students. Data collection techniques were carried out using observation, questionnaires, and interviews. Data analysis techniques using qualitative and quantitative descriptive analysis. The results showed that the English e-module product received a score of 4.00 from the material expert and a score of 3.60 from the media expert, which means that this product is feasible to use. This English e-module has also been tested on students and is proven to increase their understanding of learning English through their average score of 89. Thus, this English e-module provides benefits in an English-based learning model. Technology for Generation Z because of its effectiveness and practicality.